A novel sheet topology in the structure of kamitugaite, PbAl[(UO2)5(PO4)2.38(AsO4)0.62O2(OH)2](H2O)11.5 - Plasil,J. (Journal of Geosciences, 2017)
Kamitugaite is a rare supergene uranyl phosphate of aluminum and lead occurring at the Kobokobo pegmatite in the Sud-Kivu Province, Democratic Republic of Congo; its structure has remained unknown until now. Based on single-crystal X-ray diffraction data carried out on the type specimen of kamitugaite (no. 13986, Royal Museum for Central Africa, Tervuren), it is triclinic, space group P-1, with a = 9.0296(8), b = 10.9557(8), c = 15.8249(15) Å, α = 89.585(7)°, β = 85.349(8)°, γ = 84.251(7)°, V = 1552.5(2) Å3 and Z = 2. The structure was refined from diffraction data to R = 0.1074 for 2697 unique observed reflections. The structure of kamitugaite is based upon infinite sheets of uranyl and phosphate polyhedra, stacked perpendicular to c; these sheets result from edge-sharing of UO7 and UO8 bipyramids, forming chains approximately parallel to b, which are linked by (P,As)O4 tetrahedra. Such a sheet has not been observed in minerals or synthetic compounds and is related to the phosphuranylite topology; the ring symbol is 61544334. There are two distinct interlayer complexes in kamitugaite: one involving Pb2+ and H2O groups and another involving octahedrally coordinated Al3+ and isolated H2O groups. Adjacent sheets are linked a) through the Pb2+-O and H-bonds, and b) via H-bonds only in case of the interlayer with Al, the bonding differences being largely attributable to the very different stereochemistry of Pb2+ compared to Al3+. The unique combination of these two elements is probably a key reason for the scarcity of kamitugaite.
Keywords: kamitugaite; uranyl phosphate; crystal structure; topology